2015
DOI: 10.1016/j.ifacol.2015.09.614
|View full text |Cite
|
Sign up to set email alerts
|

Centralised versus Decentralised Control Reconfiguration for Collaborating Underwater Robots

Abstract: The present paper introduces an approach to fault-tolerant reconfiguration for collaborating underwater robots. Fault-tolerant reconfiguration is obtained using the virtual actuator approach, Steffen (2005). The paper investigates properties of a centralised versus a decentralised implementation and assesses the capabilities under communication constraints between the individual robots. In the centralised case, each robot sends information related to its own status to a unique virtual actuator that computes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A more detailed review of their properties and an example of practical application can be found in [5,6]. In the present work, we use a decentralized agent control strategy, as it is more reliable and fault-tolerant from the safety perspective.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed review of their properties and an example of practical application can be found in [5,6]. In the present work, we use a decentralized agent control strategy, as it is more reliable and fault-tolerant from the safety perspective.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, centralized methods are the most common, and they make a decision through all the information about the systems, being the drawback that fast communication methods and massive data elaboration are needed. On the other hand, decentralization allows each agent to process its information locally but lacks a complete vision of the whole environment (Furno et al 2015;Son 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The objective in cooperative control is to design a distributed control strategy using only local information, so that the aggregate system achieves specified behaviors, such as flocking, [4,5] synchronization, [6,7] coordination, [8,9] rendezvous, and formation control. The present and future practical applications of multi-robot systems span different areas, such as: underwater and space exploration (underwater cultural heritage recovery, coordination of clusters of satellites, and synchronization of spacecrafts); [10,11] hazardous environments (search and rescue missions, and military operations); [12,13] and service robotics (commercial cleaning, material handling, furniture assembly, etc.). [14][15][16] A fundamental approach to achieve a cooperative behavior is consensus.…”
Section: Introductionmentioning
confidence: 99%